2022
DOI: 10.1039/d2nr02064e
|View full text |Cite
|
Sign up to set email alerts
|

Reverse anti-breast cancer drug resistance effects by a novel two-step assembled nano-celastrol medicine

Abstract: CNPs synthesized by a simple and convenient method without involve any nano-carrier and toxicity organic solvent. Meanwhile, the functional CNPs with chitosan could be endocytosed by their nano-characterization to realize drug resistance reversal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…As it has been confirmed that Cela can play an apoptosis inducing role in a variety of tumor cells (Medatwal et al., 2020 ; Xiao et al., 2022 ), Annexin V/PI staining was adopted to evaluate the apoptosis-inducing effect of free Cela and C-TL/HA on HepG2 cells. As shown in Figure 5D , the apoptosis rate of C-TL/HA group was significantly higher than that of free Cela group ( p < 0.001), indicating that the enhanced proapoptotic effect of C-TL/HA might be related to the higher cellular uptake of Cela and the effective initiation of apoptosis induced by mitochondrial pathway.…”
Section: Resultsmentioning
confidence: 99%
“…As it has been confirmed that Cela can play an apoptosis inducing role in a variety of tumor cells (Medatwal et al., 2020 ; Xiao et al., 2022 ), Annexin V/PI staining was adopted to evaluate the apoptosis-inducing effect of free Cela and C-TL/HA on HepG2 cells. As shown in Figure 5D , the apoptosis rate of C-TL/HA group was significantly higher than that of free Cela group ( p < 0.001), indicating that the enhanced proapoptotic effect of C-TL/HA might be related to the higher cellular uptake of Cela and the effective initiation of apoptosis induced by mitochondrial pathway.…”
Section: Resultsmentioning
confidence: 99%
“… 14 , 15 In order to improve antitumor efficacy, there is an increasing emphasis on combination therapy, ie, the use of two or more drugs with different therapeutic mechanisms to enhance antitumor efficacy through synergistic effects. 16 , 17 The efficacy of free drug combinations is usually compromised by insufficient bioavailability, and nanocarrier co-delivery systems are potentially advantageous in combination therapy. To date, many nanosystems have been proposed to deliver two or more molecules with synergistic pharmacological activity to different cellular targets in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many nanosystems have been proposed to deliver two or more molecules with synergistic pharmacological activity to different cellular targets in the tumor microenvironment. 16 , 17 For example, small dendritic macromolecules loaded with adriamycin (PAMAM-ss-DOX) (DP) were synthesized and encapsulated into pH-responsive nanoliposomes along with adjuvants toll-like receptor 7/8 (TLR7/8) agonist resiquimod (R848) and losartan (LOS). 18 Among them, LOS effectively reduced the activity of CAF.…”
Section: Introductionmentioning
confidence: 99%
“…[ 42–44 ] Recent research found that advanced catalytic nanomaterials (including nanozymes) not only have the characteristics of high drug payload, low toxicity, good biocompatibility, and specific drug delivery through passive (enhanced permeability and retention, EPR) or active targeting but also own the capability of continuous releasing NO through catalytic reaction, which might significantly increase the feasibility of NO‐based therapies. [ 45–48 ] Within this context, there have been many efforts in designing and fabricating NO‐releasing platforms based on catalytic nanomaterials, and therefore, significant progress has been achieved in many biomedical applications.…”
Section: Introductionmentioning
confidence: 99%